The Wars of the French Revolution, 1792-1801 - Esdaile, Charles J.
1 online resource (360 pages)
Keywords: The Wars of the French Revolution, 1792-1801 offers a comprehensive and jargon-free coverage of this turbulent period and unites political, social, military and international history in one volume. Carefully designed for undergraduate students, through twelve chapters this book offers an introduction to the origins and international context of the French Revolution as well as an in-depth examination of the reasons why war began. Aspects unpicked within the book include how France acquired a de facto empire stretching from Holland to Naples; the impact of French conquest on the areas concerned; the spread of French ideas beyond the frontiers of the French imperium; the response of the powers of Europe to the sudden expansion in French military power; the experience of the conflicts unleashed by the French Revolution in such areas as the West Indies, Egypt and India; and the impact of war on the Revolution itself. Offering extensive geographical coverage and challenging many preconceived ideas, The Wars of the French Revolution, 1792-1801 is the perfect resource for students of the French Revolution and international military history more broadly.